Relationship between trade and development, with particular reference to the service trade : how the WTO may benefit from experience under the GATT - Abu-Akeel, Aly K. (2000)
Evaluates, from a legal/institutional standpoint, how, in handling issues of trade and development, with particular reference to the service trade, the World Trade Organization may benefit from the experience gained so far in that area under the GATT.